EURATOM—Community in a crisis - Fritz Hellwig (Intereconomics, 1969)
The founders of the European Atomic Energy Community (EURATOM) acted “In the conviction that only a concerted action … offers the chance to achieve a performance which corresponds to the creative forces of its members”. This sentence is still anchored in the treaty of the Community, but it seems to disapper from its activities. National egoism has oppressed stronger and much earlier than in the EEC the work of EURATOM. The dispute about the research programmes is followed by the quarrel over the finances. Lack of determination to make decisions and adherence to national competences are endangering the existence of the Community. We discussed with Dr Hellwig, who is competent in the EEC Commission for the sectors of energy, research and technology, the destiny of EURATOM.
Keywords: 330; Euratom; Interview